Financial incentives to encourage healthy behaviour: an analysis of UK media coverage. (20th July 2011) - Parke, Hannah; Ashcroft, Richard; Brown, Rebecca; Marteau, Theresa M; Seale, Clive
Abstract Background Policies to use financial incentives to encourage healthy behaviour are controversial. Much of this controversy is played out in the mass media, both reflecting and shaping public opinion. Objective To describe UK mass media coverage of incentive schemes, comparing schemes targeted at different client groups and assessing the relative prominence of the views of different interest groups. Design Thematic content analysis. Subjects National and local news coverage in newspapers, news media targeted at health‐care providers and popular websites between January 2005 and February 2010. Setting UK mass media. Results The study included 210 articles. Fifteen separate arguments favourable towards schemes, and 19 unfavourable, were identified. Overall, coverage was more favourable than unfavourable, although most articles reported a mix of views. Arguments about the prevalence and seriousness of the health problems targeted by incentive schemes were uncontested. Moral and ethical objections to such schemes were common, focused in particular on recipients such as drug users or the overweight who were already stereotyped as morally deficient, and these arguments were largely uncontested. Arguments about the effectiveness of schemes and their potential for benefit or harm were areas of greater contestation. Government, public health and other health‐care provider interests dominated favourable coverage; opposition came from rival politicians, taxpayers' representatives, certain charities and from some journalists themselves. Conclusions Those promoting incentive schemes for people who might be regarded as 'undeserving' should plan a media strategy that anticipates their public reception.